2024
DOI: 10.1007/s11482-024-10280-6
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Roles of Mindfulness in Marriage and Mindfulness in Parenting in the Relationship Between Parents’ Dispositional Mindfulness and Emotion Regulation of Their Children

Ezgi Güney Uygun,
Seher Merve Erus

Abstract: The fact that primary school is a pre-adolescent period makes it important in terms of regulating emotions. The beginning signals of adolescence occur during this period. It is clear that this challenging process of emotion regulation is linked to age and development, along with parental characteristics and the interactions of the child with the parent. It is believed that researching the variables that influence emotion regulation can help individuals maintain healthy social interactions throughout their jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The results showed that parental autonomy support was positively associated with mindfulness. One possible reason is that parental autonomy support create a positive and supportive family environment, and individuals in autonomy-supportive environments are more likely to receive support and understanding from their parents, which helps them recognize themselves more deeply and comprehensively and cope with their own feelings with positive mental states and emotional responses ( Lan and Wang, 2020 ; Uygun and Erus, 2024 ), thus making them easier to achieve and maintain a positive state of mindfulness. This is consistent with previous findings that individuals with autonomy support have more possibilities to address problems independently, are listened to and respected more often, and are more involved in planned activities or behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that parental autonomy support was positively associated with mindfulness. One possible reason is that parental autonomy support create a positive and supportive family environment, and individuals in autonomy-supportive environments are more likely to receive support and understanding from their parents, which helps them recognize themselves more deeply and comprehensively and cope with their own feelings with positive mental states and emotional responses ( Lan and Wang, 2020 ; Uygun and Erus, 2024 ), thus making them easier to achieve and maintain a positive state of mindfulness. This is consistent with previous findings that individuals with autonomy support have more possibilities to address problems independently, are listened to and respected more often, and are more involved in planned activities or behaviors.…”
Section: Discussionmentioning
confidence: 99%